The Influence Of Sharia Management, Information Technology And Leadership On Performance Effectiveness (Study On Employees Of Pt. Sentosa Deli Mandiri Medan) - Ichsan, Reza Nurul (Moneter: Jurnal Keuangan dan Perbankan, 2023)
The development of human development benchmarks the progress of technology-based science and the Internet, and employees who are assets of the Company, to carry out the goals and objectives expected by the Company, therefore the Company and employees together carry out their responsibilities and fulfill their respective rights and obligations in accordance with the standard operating system (SOP) set by the Company, employees are guided to do work professionally, so this research is about the Influence of Sharia Management, Information Technology and Leadership on Performance Effectiveness in Employees of PT Sentosa Deli Mandiri Medan, Research methodology This research is quantitative research, with an explanation approach (explanation research). Explanatory research (explanation research) is a type of research in which the researcher explains the causal relationship between variables through hypothesis testing. The results of the research on the influence of Sharia Management on Performance Effectiveness, the results of the analysis show that partially it has a positive and significant effect. The results of the analysis of the correlation coefficient of direct influence show the effect of Sharia Management on Performance Effectiveness, which means that Sharia Management on Performance Effectiveness in Employees of PT. Sentosa Deli Mandiri Medan is a high effect; The effect of information technology on Performance Effectiveness in Employees of PT. Sentosa Deli Mandiri Medan, the results of the analysis show that partially has a positive and significant effect; The effect of Sharia Management, Information Technology and Leadership on Performance Effectiveness in Employees of PT. Sentosa Deli Mandiri Medan, giving the conclusion that it has a positive and significant effect.